(untitled) (Práxis Educativa, 2024)
Science teachers reveal a set of assumptions and evaluative subjectivities. Therefore, the objective is to know their perspectives on educational evaluation, that is, what teachers think and do when evaluating. A mixed approach methodology, sequential design is applied. In the quantitative phase, a questionnaire was administered to a sample of 298 teachers in the area of Science and Technology, to investigate the functions, contents, moments and evaluation procedures. For the qualitative phase, six teachers were interviewed about their pedagogical, didactic, epistemic and evaluative positions; exploring their subjectivities. The results show the symbolic nature of the evaluation, the prioritization of certain evaluative aspects that reveal the recurrence of “traditional” and “modern” conceptions and practices that coexist in the being and work of a teacher, making ambiguities evident. The low effectiveness of the changes promoted and the confusion in making pedagogical decisions are expressed. Keywords: Evaluative perspectives. Science teaching. Secondary education.